Optimizing the Utilization of Information Technology and Implementing Hybrid Organizations in Health Service Innovation - Sofjan Aripin; Rulinawaty Rulinawaty; Dewi Maharani Rachmaningsih; Cherly Kemala Ulfa (Universitas Dharma Wacana, 2022)
Policy is a reference for the government bureaucracy in carrying out its functions and duties. Public service phenomena and problems are a serious concern in Indonesia, and this is indicated by how low public expectations are for public services. There are still many problems with public services in Indonesia, and this causes shallow public expectations of public services. The common public choice of alternative public services is also one of the causes of the birth of a hybrid organization. Besides that, during the era of disruption known as the industrial revolution 4.0, public policy could not be separated from public service innovation using communication and information technology through the concept of e-government for the creation of good public services. This is also included in the invention of health services for the community. Therefore, this study takes the theme of Optimizing the Utilization of Information Technology and Application of Hybrid Organizations in Health Service Innovation. This study uses a qualitative approach using a case study analysis strategy at the First Level Health Facility in the Nunukan sub-district, the Nunukan district, North Kalimantan. The results show that the use of Information and Communication Technology in public services, especially in health services, is proven to be able to help the community in terms of efficiency, effectiveness, and accountability through the availability of accurate and comprehensive patient health information, so that providers can provide the best possible treatments. Meanwhile, in terms of providing health insurance costs amid limited resources owned by the government, the Hybrid Organization concept is a solution to the problem wherein a hybrid system, financing comes from the basis of public resources, and non-profit organizations and the form of control requires government and private supervision as well as good practices professionally organized